Bioinspired liquid-infused surface for biomedical and biosensing applications - Yang, Yuemeng; Zhu, Qinglin; Xu, Li-Ping; Zhang, Xueji (Frontiers in Bioengineering and Biotechnology, 2022)
Nature always inspires us to develop advanced materials for diverse applications. The liquid-infused surface (LIS) inspired by Nepenthes pitcher plants has aroused broad interest in fabricating anti-biofouling materials over the past decade. The infused liquid layer on the solid substrate repels immiscible fluids and displays ultralow adhesion to various biomolecules. Due to these fascinating features, bioinspired LIS has been applied in biomedical-related fields. Here, we review the recent progress of LIS in bioengineering, medical devices, and biosensing, and highlight how the infused liquid layer affects the performance of medical materials. The prospects for the future trend of LIS are also presented.